A Human Rights Life-World? - Ben Dorfman (Akademisk Kvarter, 2012)
The article considers the concept of the life-world as something real – a “surrounding” environment. It also uses “life-world” metaphorically, as it asks: when we think about a concept such as human rights, where do we find ourselves? How do we have such concepts “at hand,” and what are the ways in which the presentation of rights ideas is so rich – “thick” might be another term – that it seems natural they’re there? And it answers "À la the notion of life-world, the idea is outlining a conceptual and tactile space in which human rights appear “everywhere.” Human rights sit to the left and right of us, occupying the sinews of fact and fiction." And it concludes that human rights were once an inclusive discourse, spoken by the powerful and the not. The “inclusiveness” of rights dissipated in the mid-twentieth century, however.